The Use of Self Assessment in Improving Students Ability in Writing English Skill - Uswatun Hasanah (Ethical Lingua: Journal of Language Teaching and Literature, 2015)
This research aims at finding out The Use of Self-Assessment in Improving Writing English Skill of the Students at English Education Department of STAIN Watampone academic year 2013/2014. The specific objective of the research is to find out whether or not the use of self-assessment improves students’ performance in writing English skill. The research method employed quasi experimental research. The samples consist of 40 students which belonged to two groups; experimental and control group. The research data were collected using two kinds of instruments: the writing test which was given to the both groups and questionnaires of learners’ self assessment which was given only to the experimental group. The research result indicated that: the use of self-assessment in writing English skill is more effective in improving students’ ability. The result of post test of both group improved, but the use of self assessment gave better effect than conventional way. It was proved by the result of the mean score of post test of experimental was higher than the control group in writing skill. It is suggested to the English teacher that the use of learners’ self assessment as one of alternative strategy in teaching writing in order to improve students’ writing ability. In addition the students can take responsibility for their own learning.